Vitamin C: an experimental and theoretical study on the gas‐phase structure and ion energetics of protonated ascorbic acid. (7th October 2016) - Ricci, Andreina; Pepi, Federico; Cimino, Paola; Troiani, Anna; Garzoli, Stefania; Salvitti, Chiara; Di Rienzo, Brunella; Barone, Vincenzo
Abstract : In order to investigate the gas‐phase mechanisms of the acid catalyzed degradation of ascorbic acid (AA) to furan, we undertook a mass spectrometric (ESI/TQ/MS) and theoretical investigation at the B3LYP/6‐31 + G(d, p) level of theory. The gaseous reactant species, the protonated AA, [C6 H8 O6 ]H +, were generated by electrospray ionization of a 10 −3 M H2 O/CH3 OH (1 : 1) AA solution. In order to structurally characterize the gaseous [C6 H8 O6 ]H + ionic reactants, we estimated the proton affinity and the gas‐phase basicity of AA by the extended Cooks's kinetic method and by computational methods at the B3LYP/6‐31 + G(d, p) level of theory. As expected, computational results identify the carbonyl oxygen atom (O2) of AA as the preferred protonation site. From the experimental proton affinity of 875.0 ± 12 kJ mol −1 and protonation entropy Δ S p 108.9 ± 2 J mol −1 K −1, a gas‐phase basicity value of AA of 842.5 ± 12 kJ mol −1 at 298 K was obtained, which is in agreement with the value issuing from quantum mechanical computations. Copyright © 2016 John Wiley & Sons, Ltd.